2017
DOI: 10.1002/jbm.a.36101
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of vascularization of a subcutaneous scaffold applicable for pancreatic islet‐transplantation enhances immediate post‐transplant islet graft function but not long‐term normoglycemia

Abstract: The liver as transplantation site for pancreatic islets is associated with significant loss of islets, which can be prevented by grafting in a prevascularized, subcutaneous scaffold. Supporting vascularization of a scaffold to limit the period of ischemia is challenging and was developed here by applying liposomes for controlled release of angiogenic factors. The angiogenic capacity of platelet‐derived growth factor, vascular endothelial growth factor, acidic fibroblast growth factor (aFGF), and basic FGF were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…This was the main rational to test the impact of SCFAs on β-cells [29,30]. In addition, we tested how SCFAs can reduce oxidative and nitrosative stress in human islets and β-cells after exposure to STZ [31]. We demonstrate the strong viability promoting effects and protection against oxidative and nitrosative stress by both acetate and butyrate at lower concentrations of 1 mM, while higher concentrations had adverse effects.…”
Section: Discussionmentioning
confidence: 91%
“…This was the main rational to test the impact of SCFAs on β-cells [29,30]. In addition, we tested how SCFAs can reduce oxidative and nitrosative stress in human islets and β-cells after exposure to STZ [31]. We demonstrate the strong viability promoting effects and protection against oxidative and nitrosative stress by both acetate and butyrate at lower concentrations of 1 mM, while higher concentrations had adverse effects.…”
Section: Discussionmentioning
confidence: 91%
“…It has been suggested that stimulation of angiogenesis is critical to successful subcutaneous islet transplantation (47,51,55,68), prompting investigation of a number of vascularization strategies. Specifically, vascularization using empty devices or other synthetic materials pretransplantation of islets (16,35,45,46,61,62), oxygen generators (37,38), and cotransplantation of soluble factors (e.g., fibroblast growth factor, hepatocyte growth factor, and vascular endothelial growth factor) (29, 71) or cells (e.g., fibroblasts, mesenchymal stem cells, and endothelial cells) (48,49,71) have all been explored with variable success. For most of these strategies, there is a 1-to 4-wk posttransplantation delay for animals to achieve normoglycemia as islet health and site vascularization and mass transport properties presumably become sufficient for normal glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, we have applied fibrin in polymeric scaffolds that serve as an artificial transplantation site for pancreatic islets under the skin [ 86 ]. This resulted in enhanced vascularisation and engraftment of islets, reducing the number of islets needed to achieve normoglycaemia in mice [ 86 , 87 ]. This might be explained by specific interactions of fibrin with some integrins in islets, including α v β 1 , which is known to be important for the function of transplanted islets [ 88 ].…”
Section: Ecm Structures That Might Support Islet Functionmentioning
confidence: 99%
“…Fibrin can also upregulate α v β 3 integrin expression, which prevents beta cell apoptosis [ 80 , 83 ]. Thus, fibrin is an excellent candidate for exogenous addition to islet grafts to enhance their survival [ 86 , 87 ].…”
Section: Ecm Structures That Might Support Islet Functionmentioning
confidence: 99%